Trade Elasticities in the Middle East and Central Asia : What is the Role of Oil? - Billmeier, Andreas (IMF Working Papers; Working Paper, 2008)
The analysis in this paper suggests that import and export volume elasticities are markedly lower in oil-exporting Middle East and Central Asian countries than in non-oil countries in the region. A key implication of this finding is that a real appreciation of the exchange rate in oil-exporting countries would achieve little in terms of expenditure switching: an appreciation does not boost imports and non-oil exports constitute only a small share of GDP and total trade in these countries. Therefore, while a real appreciation lowers the current account surplus of oil-exporting countries through valuation effects, the contribution to lowering global imbalances may be more limited.